Problematics of Arabic Learning through e-Learning and Its Solution at Senior High School - Dedi Mulyanto; Sarah Fauziah; Arifin, Laode Muhammad Alfateh (Institut Agama Islam Negeri (IAIN) Kediri, 2024)
The objectives of this study are: 1. To explain the problems of learning Arabic through E-learning for class XI IPA at MAN 1 Sragen, Central Java, Academic Year: 1441-1442 H, 2. To explain about solving these problems. This type of research is a qualitative descriptive study. In collecting the data, the researcher used three methods, namely: the interview method, the observation method, and the documentation method. Researchers used Miles and Huberman's analysis with three steps: data collection, data presentation, and conclusion. The results of the data analysis stated that: 1) Arabic learning problems through E-learning for class XI IPA consists of several aspects: a) Problems in terms of teachers: The teacher leaves several steps contained in the language learning method Arabic through E-learning, b) Problems in terms of students: Lack of student interest in learning Arabic through E-learning, c) Problems in terms of E-learning media include: E-learning media is a learning application that requires supporting tools, such as Android, Computers, and Internet Signals, 2) Problem-solving in the learning problem consists of several aspects: a) Problem-solving from the teacher's point of view. The teacher must use the Arabic teaching method through E-learning properly and correctly. b) The solutions to students' problems are the teachers must increase student motivation in learning Arabic through E-learning, c) Completion in terms of E-learning media. Teachers and students must prepare supporting tools in the Arabic learning process through E-learning.